Hypercaloric low-carbohydrate high-fat diet protects against the development of nonalcoholic fatty liver disease in obese mice in contrast to isocaloric Western diet - Charlot, Anouk; Bringolf, Anthony; Mallard, Joris; Charles, Anne-Laure; Niederhoffer, Nathalie; Duteil, Delphine; Pagano, Allan F.; Geny, Bernard; Zoll, Joffrey (Frontiers in nutrition (Lausanne), 2024)
Obesity and metabolic complications, such as type 2 diabetes and nonalcoholic fatty liver disease (NAFLD), are one of the greatest public health challenges of the 21st century. The major role of high sugar and carbohydrate consumption rather than caloric intake in obesity and NAFLD pathophysiology remains a subject of debate. A low-carbohydrate but high-fat diet (LCHFD) has shown promising results in obesity management, but its effects in preventing NAFLD need to be detailed. This study aims to compare the effects of a LCHFD with a high-fat high-sugar obesogenic Western diet (WD) on the progression of obesity, type 2 diabetes, and nonalcoholic fatty liver disease. Male C57BL/6J mice were initially fed a WD for 10 weeks. Subsequently, they were either switched to a LCHFD or maintained on the WD for an additional 6 weeks. Hepatic effects of the diet were explored by histological staining and RT-qPCR. After the initial 10 weeks WD feeding, LCHF diet demonstrated effectiveness in halting weight gain, maintaining a normal glucose tolerance and insulin levels, in comparison to the WD-fed mice, which developed obesity, glucose intolerance, increased insulin levels and induced NAFLD. In the liver, LCHFD mitigated the accumulation of hepatic triglycerides and the increase in Fasn relative gene expression compared to the WD mice. Beneficial effects of the LCHFD occurred despite a similar calorie intake compared to the WD mice. Our results emphasize the negative impact of a high sugar/carbohydrate and lipid association for obesity progression and NAFLD development. LCHFD has shown beneficial effects for NAFLD management, notably improving weight management, and maintaining a normal glucose tolerance and liver health.